IMPLEMENTASI E-KASIR PADA INDUSTRI PERCETAKAN DAN PERIKLANAN - Adhiatma, Novri; Ikhsan, Muhammad (Jurnal Simantec, 2024)
Various industries have started using e-cashier systems as a result of advances in information technology. Although e-cashier speeds up the transaction process, there are still important issues related to data security, system integration, and good inventory management. Lack of knowledge about the application of appropriate technology and system limitations in handling large transaction volumes are major problems in implementing this system. The purpose of this study is to create an e-cashier system based on information technology, RN Gallery is a company engaged in printing and advertising, in the financial transaction process still uses manual methods that are time-consuming and prone to errors. The system that is running in the recording process each uses weekly or monthly notes and reports recorded in the ledger. Recording orders, calculating prices, and payments are still done manually. The Waterfall method is used in software development. This method was chosen because it can provide structured and clear steps for system design and implementation. The results of the analysis carried out using the PIECE method, where the main problems that need to be fixed are found Renewability. Combining the e-cashier system with real-time inventory management and improving the data security system. This study also offers knowledge about the implementation of a more efficient and secure e-cashier system and evaluates how effective the Waterfall method and PIECES method are in creating an e-cashier system. The results of testing the E-Cashier application using blackbox testing show that the system has worked according to its function from 10 features tested showing results as expected.Keywords: Blackbox Testing, Transaction Efficiency, Inventory Management, Waterfall Method, PIECES Method of E-Cashier System